Draft Genome Sequences of Antibiotic-Resistant Commensal Escherichia coli - Garrett, Meghan (Genome Announc, 2014)
Antimicrobial resistance is a significant public health issue. We report here the draft genome sequences of three drug-resistant strains of commensal Escherichia coli isolated from a single healthy college student. Each strain has a distinct genome, but two of the three contain an identical large plasmid with multiple resistance genes.